The Effect of the Default Risk of Debt on the Earnings Response Coefficient. - Dhaliwal, Dan S.; Reynolds, Stanley S. (The Accounting Review, 1994)
Abstract Examines the effect of the default risk of debt on the relation between accounting earnings and stock returns. Correlation between equity valuation and the earnings response coefficient (ERC); Cumulative abnormal returns; Equity beta; Earnings persistence; Unexpected earnings.